Avalanche prevention release system GAZEX as a tool to control of snow discharge in small portions - D. V. Tetekin; N. I. Osokin; N. A. Volodicheva (Лëд и снег, 2015)
GAZEX system is used in Russia from 2002 to release artificial avalanches. The experience of realization of this system in the Krasnaya Polyana region (the place of Olympic Winter Games of 2014) is described in the article in comparison with application of nowadays and earlier systems.